Consistency analysis of multidimensional gonio-spectrophotometric measurements in interlaboratory comparisons. (14th June 2016) - Ferrero, A; Campos, J; Bernad, B; Pons, A; Hernanz, M L; Martínez-Verdú, F M; Höpe, A
Abstract: The spectral bidirectional reflectance distribution function (BRDF) is the key quantity to specify the spectral reflectance of materials for any condition of irradiation and detection, and its characterization is quite important for surfaces with a high dependence on these conditions, such as iridescent coatings. In order to evaluate the calibration and measurement capabilities (CMC) of National Metrology Institutes with the ability to measure the spectral BRDF, a case study interlaboratory comparison is in progress. Spectral BRDF has both spectral and geometric dependence, and this multidimensionality must be treated in the comparison to provide useful information to the participants about their CMCs. A data analysis method for the comparison is presented in this work, which was tested by simulations for different scenarios. The proposed method assesses whether the experimental data from each participant are consistent with those from the others. Finally, one-dimensional and multidimensional degrees of equivalence are defined, which should allow systematic deviations of spectral and geometric nature to be identified.